Sexual Risk Behaviour Among HIV-Positive Persons in Kumasi, Ghana - Ncube, NM (Ghana Medical Association, 2012)
OBJECTIVES: To assess the prevalence and predictors of sexual risk behaviours among HIV-positive individuals in clinical care in Kumasi, Ghana. DESIGN: Cross-sectional survey of 267 (43 males and 224 females) HIV-positive individuals attending Kumasi South Regional Hospital. METHODS: An interviewer-administered questionnaire was used to asses demographic and health characteristics, HIV/AIDS knowledge, attitudes, and beliefs and sexual risk behaviours. RESULTS: Forty-four percent of the sample reported having sex after testing positive for HIV. Of the 175 participants with regular sex partners, 24% had HIV-positive partners. Majority (67%) had HIV-negative partners (serodiscordant couples) or partners of unknown status. More than half (51%) of the study population with regular sex partners reported that they had unprotected anal or vaginal sex. Participants who scored < 50% on the HIV/AIDS knowledge scale were 90% less likely to have used condoms during their last sexual intercourse. Disclosure of HIV status was associated with protective patterns of condom use (OR=2.2; 95% CI: 1.3–12.9). Participants on ARV were 80% less likely to have used condoms during the last sexual intercourse (OR=0.2; 95% CI: 0.04–0.6). CONCLUSION: The high rates of sexual risk behaviour among HIV-positive individuals in this sample place others at risk of HIV infection. It also places these HIV positive individuals at risk for infection with sexually transmitted infections and super-infection with other HIV strains. These findings highlight the need to integrate HIV prevention in routine medical care in Ghana.